The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1515/mgmc.1995.18.9-10.451
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Coordination Compounds: Classification and Analysis of Crystallographic and Structural Data

Abstract: Cadmium chemistry is an important area of research from both an industrial and environmental point of view. This review surveys the structural determination of over six hundred complexes of cadmium. The coordination numbers observed range from two to eight with six occuring most frequently, and lower values mostly associated with carbon donor ligands. The most common donor atoms in the higher coordination number complexes are Ν, Ο and CI. A range of derivatives from dimers to polymers contain two or more cadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 304 publications
0
10
0
Order By: Relevance
“…Even if Cd has been shown to occur in 2-, 3-, 4-, 5-, 6-, 7-, or 8-coordination in low molecular weight organic molecules, 6-and 4-coordination geometries predominate. Cadmium bonded to O is usually 6-coordinated, and Cd bonded to S is usually 4-coordinated (28). In Table 3 literature data on Cd distances in 4-and 6-coordinated compounds are presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if Cd has been shown to occur in 2-, 3-, 4-, 5-, 6-, 7-, or 8-coordination in low molecular weight organic molecules, 6-and 4-coordination geometries predominate. Cadmium bonded to O is usually 6-coordinated, and Cd bonded to S is usually 4-coordinated (28). In Table 3 literature data on Cd distances in 4-and 6-coordinated compounds are presented.…”
Section: Resultsmentioning
confidence: 99%
“…Above the absorption edge a cubic spline fit was used to remove the background, and the data were k 3 -weighted to enhance the higher k values. Data were fitted by theoretical EXAFS amplitudes and phase functions of mixed models for Cd-S, Cd-O, and Cd-C bonding, on the basis of structural parameters from well-defined organic and inorganic com-pounds (28)(29)(30), and generated by FEFF 7.0 (31). The fitting was done in two steps: (1) After isolation of the first major peak (0.4-2.38 Å) in R-space (Fourier transforms), data backfiltered to k-space were used to determine bond distances (R) for the contribution of O/N and S atoms in the first coordination shell.…”
Section: Ion Activity Measurements With An Ion-selective Electrode (Ise)mentioning
confidence: 99%
“…Calcium is a poor activator of MntR because it has low affinity for the A site, and zinc is unable to activate MntR because it fails to adopt the correct coordination geometry in that site. It is risky to extend these observations to other metal ions, since additional factors may come into play, but it is worth re-emphasizing that, among the divalent first row transition metal ions in octahedral environments, high spin Mn 2+ has the largest ionic radius (38), and Mn 2+ is unusually flexible with respect to its coordination geometry (51). Thus, the selectivity of MntR for Mn 2+ over Fe 2+ as observed in vivo and in vitro (8,15,17), may be based on the geometry and size in the metal-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…ascribed to the overall size of these sites and the capacity of d 10 Cd 2+ to adopt a variety of geometries (51).…”
mentioning
confidence: 99%
“…The average coordination numbers (CN) for the preMD, LowEMD, and postMD Kln–Cd models were 6.0 (±0.0), 5.3 (±1.2), and 5.0 (±0.0), respectively. In general, Cd 2+ in aqueous solutions and as a hydrated surface complex is assumed to be hexacoordinated. Among a wide range of inorganic and organometallic Cd compounds, CN 6 is the most common geometry followed by CN 4, with five-coordinated compounds being relatively rare; however, distortion of the CN 6-coordinating environment around Cd is common. In the experimental XAFS analysis of Vasconcelos et al assuming one shell of O atoms, they reported an average N of 4.9 ± 0.3 Cd atoms for sorption spectra at pH 8 and 9 for different fit models, whereas one spectrum at pH 7 was fit with 5.9 ± 0.2 Cd atoms.…”
Section: Resultsmentioning
confidence: 99%